2021
DOI: 10.14245/ns.2142750.375
|View full text |Cite
|
Sign up to set email alerts
|

Five-Repetition Sit-to-Stand Test Performance in Healthy Individuals: Reference Values and Predictors From 2 Prospective Cohorts

Abstract: Objective: The 5-repetition-sit-to-stand (5R-STS) test is an objective test of functional impairment- commonly used in various diseases, including lumbar degenerative disc diseases. It is used to measure the severity of disease and to monitor recovery. We aimed to evaluate reference values for the test, as well as factors predicting 5R-STS performance in healthy adults.Methods: Healthy adults ( > 18 years of age) were recruited, and their 5R-STS time was measured. Their age, sex, weight, height, body mass i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 61 publications
3
15
4
Order By: Relevance
“…Similarly to a population of healthy adult individuals, increased height of patients with LDD correlated with worse 5R-STS performance despite the standardized seat of 43cm height. [14] This agrees with a study on stroke survivors, which showed that seat height lower than knee height increased the 5R-STS [18] Therefore, the height of a patient with LDD must be taken into account when interpreting the 5R-STS time and ideally the patient should be sat at knee-height level, or height-adjusted test times should be calculated. [18,19] Multiple studies demonstrated a signi cant positive correlation between age and 5R-STS performance in adult individuals, however the participants were often much older than patients from our cohort or categorized into either 20-29 or 80-85 age groups, missing the 48-year mean age of our participants.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similarly to a population of healthy adult individuals, increased height of patients with LDD correlated with worse 5R-STS performance despite the standardized seat of 43cm height. [14] This agrees with a study on stroke survivors, which showed that seat height lower than knee height increased the 5R-STS [18] Therefore, the height of a patient with LDD must be taken into account when interpreting the 5R-STS time and ideally the patient should be sat at knee-height level, or height-adjusted test times should be calculated. [18,19] Multiple studies demonstrated a signi cant positive correlation between age and 5R-STS performance in adult individuals, however the participants were often much older than patients from our cohort or categorized into either 20-29 or 80-85 age groups, missing the 48-year mean age of our participants.…”
Section: Discussionsupporting
confidence: 87%
“…It has been previously suggested that increased BMI, increased age and being female are a signi cant positive prognostic factor for 5R-STS performance in healthy individuals, which is also in agreement with proven risk factors for development of LDD. [14,24,31] Contrary to expectations, no such correlation was identi ed for patients with LDD. It may be theorized that once a symptomatic LDD pathology requiring surgical intervention develops, variation in 5R-STS time is no longer signi cantly correlated with basic demographic characteristics in contrast to spine-healthy individuals but predominantly in uenced by the pathology.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The results indicate that FTSTS is a simple physical function assessment that can be used in clinical practice to estimate the decline in 6 MWD in patients with pancreatic cancer. A previous study on 6 MWD and STS in women with breast cancer indicated a significant correlation [40]. This could be a useful method of assessment for busy clinicians and physical therapists to understand the decline in patients' physical function.…”
Section: Discussionmentioning
confidence: 82%
“… 15 The protocol for 5×STS is five repetitions of sitting on an armless chair of standard height (48 cm) and full standing up, as fast as possible without using the upper limbs. 41 The time from the initial stand to the completed fifth stand was recorded as the examinee’s score. The heel-raise test measures the strength of the ankle plantar flexor muscles.…”
Section: Assessment Of Muscle Quality: Muscle Strength and Performancementioning
confidence: 99%